A cross-sectional descriptive analysis of technology addiction in adolescents: associations with food addiction, emotional eating, and body weight status - Hilal Toklu Baloglu; Zeynep Caferoglu Akin (BMC, 2024)
Abstract Background This cross-sectional descriptive study aimed to determine the prevalence and risk factors of technology addiction (TA) in adolescents, as well as investigate the association of TA with food addiction and emotional eating by body weight status. Methods Adolescents (n = 1388) completed a questionnaire that featured socio-demographic characteristics, the Game Addiction Scale (GAS), the Social Media Disorder Scale (SMD), the dimensional Yale Food Addiction Scale for Children 2.0 (dYFAS‐C 2.0), and the Emotional Eating Scale Adapted for Use in Children and Adolescents (EES-C). The body mass index (BMI) Z-score was classified according to the World Health Organization. Results TA was present in one-fifth of adolescents, and boys were four times more likely to develop a digital game addiction (p < 0.001). A 1-point increase in the GAS score is associated with a 1.08-point increase in the dYFAS-C-2.0 score and a 0.5-point increase in the total EES-C score (p < 0.001). A 1-point increase in the SMD score was also related to an increased of 1.21 and 1.26, respectively (p < 0.001). All of these positive associations were significant in adolescents with overweight (p < 0.001). Conclusions Given the rapidly increasing prevalence of TA among adolescents, its association with food addiction, emotional eating, and body weight status is worrisome, and our findings shed light on the relevance of developing strategies to reduce the prevalence of TA in this population.